THREE KILOS OF COFFEE: AN AUTOBIOGRAPHY, by Manu Dibango, in collaboration with Danielle Rouard, translated by Beth G. Raps, University of Chicago Press, Chicago and London, 1994, 146pp, index, discography, photographs. - Chernoff, John M. (International Library of African Music, 1996)
pages: 137-142
Keywords: African Music